World Economy Summer 2020 - Historic contraction of the world economy - Klaus-Jürgen Gern; Philipp Hauber; Stefan Kooths; Ulrich Stolzenburg (Kiel Institute for the World Economy (IfW), 2020)
As a result of the Covid-19 pandemic, global economic activity is expected to have fallen by almost 10 percent in the first half of 2020. However, the low point seems to have been passed in the meantime, and in China the economy has even already made up a considerable part of the production slump of January and February. How quickly and decisively the global economy will recover depends not least on the epidemiological developments and on how policymakers change their epidemic policy measures in response. Assuming that the development of the pandemic allows a sustained broad-based easing of containment policies, and thanks to massive support from monetary and fiscal policy, output is expected to rebound in the second half of this year. Although the low point in global production is likely to have been reached already in April, the current year will probably see a decline of GDP (measured on the basis of purchasing power parities) of 3.8 percent, by far the sharpest contraction in the past 70 years. For 2021 we expect production to rise by 6.2 percent. The level of global production will, however, remain well below the path we expected at the beginning of the year for some time to come, due to the loss of income incurred in the course of the corona crisis and subdued investment as a result of reduced sales expectations and a diminished corporate equity base. We have drastically lowered our 2020 forecast by 5.6 percentage points compared with our regular spring forecast published in early March, but we have revised upwards by 0.3 percentage points with respect to the interim forecast presented in mid-May as incoming data suggest a slightly less negative outlook for the advanced economies.
Keywords: 330; Americas; Asia; Business Cycle World; China; Emerging Markets & Developing Countries; Europe; USA